Kajian Potensi Ekstrak Buah Mengkudu (Morinda citrifolia) sebagai Desinfektan Alami terhadap Jamur pada Ruang Penyimpanan Susu - Ratna Hadiyanti; Deden Zamzam Badruzzaman; Wowon Juanda; Yuli Astuti Hidayati (Unpad Press, 2020)
Morinda citrifolia can be used as a natural disinfectant on the milk storage space because it has an anti-fungal compound. The purpose of this study is to determine the potential of Morinda citrifolia extract as a natural disinfectant to fungi in the milk storage room, is reviewed from a decrease in the number of mushrooms and identification of the type of fungi before and after the use of Morinda citrifolia extracts. The study was conducted experimentally using a complete random design (CRD) with four treatments of P0 (without using Morinda citrifolia), P1 (15% concentration of Morinda citrifolia extract), P2 (20% concentration of Morinda citrifolia extract), P3 (concentration 25% of Morinda citrifolia extracts) and six times the replay. The observed is a decrease in the number of fungi, identifying the type of fungi before the use of Morinda citrifolia extract, identification of the type of fungi after the use of Morinda citrifolia extract. The results showed that Morinda citrifolia extract had a noticeable effect on decreasing the number of fungi in the milk storage room, with a consecutive drop percentage of P0 = 25,12%, P1 = 58,12%, P2 = 61,89%, P3 = 70,59%. The result of identification of fungi type on milk storage Chamber is Cephalosporium sp, Aspergillus ochraceus, Aspergillus flavus, Penicillium purpurogenum, Penicillium digitatum, Mucor sp. The decrease in the amount of the type of each fungus is Cephalosporium sp (68,13%), Aspergillus ochraceus (88%), Aspergillus flavu (87,94%), Penicillium purpurogenum (85,71%), Penicillium digitatum (95.73%), Mucor sp (59,57%).